RELEVANCE OF RELIGIOUS COURT DECISIONS REGARDING DISPENSATION IN CHILD MARRIAGE - Rifki Fakihudin; Pramestya Raharjanti; Muhammad Wahyu Saiful Huda (Indonesia Private Law Review)
Child marriage in Indonesia remains a significant issue and has been on the rise recently. The practice of granting marriage dispensations in Religious Courts has various legal implications. Although judges have the authority to reject applications for child marriage based on legal considerations, their decisions are not always consistent. This paper addresses two primary issues: the legal consequences of marriage dispensations for child marriages and the alignment of Religious Court decisions with positive law. Employing an empirical juridical research methodology, the research uses secondary data from literature, including laws, court rulings, and legal theories, and applies qualitative methods for data analysis. The research includes an empirical review of literature from online sources. The findings suggest that while marriage dispensation can legally validate marriages, rejected applications can be appealed to the Supreme Court. It underscores the critical role of judges in being selective and rigorous in evaluating dispensation requests to curb the rise of child marriages in Indonesia.